Novel dry pericardiocentesis: Transvenous puncture of the right ventricle with the back end of a 0.014-inch PTCA guidewire and a 1.8 Fr microcatheter - Qin, Hua-Di; Gao, Hui; Gao, Jie; Hou, Lin; Shao, Xiang-Seng; Tang, Jing-Wei; Qin, Chun-Chang (Frontiers in Cardiovascular Medicine, 2022)
Background: Dry transthoracic pericardiocentesis is challenging and carries the risk of right ventricle (RV) or coronary artery injury. The RV can usually control bleeding automatically. For example, most perforations of the RV caused by pacemaker leads are treated without open surgery. Thus, we performed a transvenous puncture of the RV for dry pericardiocentesis with the back end of a 0.014-inch percutaneous transluminal coronary angioplasty (PTCA) guidewire and a 1.8 Fr microcatheter. Methods: The back end of a 0.014-inch PTCA guidewire within a 1.8 Fr microcatheter was used to transvenously punctured through the middle of the acute margin of the RV into the pericardial space in 12 Yorkshire swine and 5 beagles. PTCA balloons of different diameters were used to dilate the puncture holes for 15 min under anticoagulation in all the animals to assess the ability of the RV to control the bleeding. Then, for 3 days, the puncture hole was dilated by a 6 Fr catheter in 9 swine and 5 dogs. Results: The puncture was successful in all the animals. After withdrawal of the 2.5-mm balloon or the 6 Fr catheter, none of the animals exhibited pericardial effusion, as observed by echocardiography. There was no sustained ventricular arrhythmia or other complications. All the animals survived. Conclusion: Transvenous puncture of the right ventricle with the back end of a 0.014-inch PTCA guidewire and 1.8 Fr microcatheter may be feasible and have a good safety margin.